Identifying acid-base and electrolyte imbalances. Issue 8 (15th August 2015) - Gooch, Michael D.
Abstract : Abstract: Acid-base and electrolyte imbalances often complicate patient management in acute care settings. Correctly identifying the imbalance and its cause is vital. This article will review the physiology of acid-base and electrolyte balance, their common disturbances, associated causes, clinical manifestations, and management implications for nurse practitioners. Abstract : Acid-base and electrolyte imbalances often complicate patient management in acute care settings. This article will review the physiology of acid-base and electrolyte balance, their common disturbances, associated causes, clinical manifestations, and management implications for nurse practitioners.